Association between imaging surveillance frequency and outcomes following surgical treatment of early-stage lung cancer. (29th November 2022) - Heiden, Brendan T; Eaton, Daniel B; Chang, Su-Hsin; Yan, Yan; Schoen, Martin W; Thomas, Theodore S; Patel, Mayank R; Kreisel, Daniel; Nava, Ruben G; Meyers, Bryan F; Kozower, Benjamin D; Puri, Varun
Abstract: Background: Recent studies have suggested that more frequent postoperative surveillance imaging via computed tomography following lung cancer resection may not improve outcomes. We sought to validate these findings using a uniquely compiled dataset from the Veterans Health Administration, the largest integrated health-care system in the United States. Methods: We performed a retrospective cohort study of veterans with pathologic stage I non-small cell lung cancer receiving surgery (2006-2016). We assessed the relationship between surveillance frequency (chest computed tomography scans within 2 years after surgery) and recurrence-free survival and overall survival. Results: Among 6171 patients, 3047 (49.4%) and 3124 (50.6%) underwent low-frequency (<2 scans per year; every 6-12 months) and high-frequency (≥2 scans per year; every 3-6 months) surveillance, respectively. Factors associated with high-frequency surveillance included being a former smoker (vs current; adjusted odds ratio [aOR] = 1.18, 95% confidence interval [CI] = 1.05 to 1.33), receiving a wedge resection (vs lobectomy; aOR = 1.21, 95% CI = 1.05 to 1.39), and having follow-up with an oncologist (aOR = 1.58, 95% CI = 1.42 to 1.77), whereas African American race was associated with low-frequency surveillance (vs White race; aOR = 0.64, 95% CI = 0.54 to 0.75). With a median (interquartile range) follow-up of 7.3 (3.4-12.5) years, recurrence was detected in 1360 (22.0%) patients. High-frequency surveillance was not associated with longer recurrence-free survival (adjusted hazard ratio = 0.93, 95% CI = 0.83 to 1.04, P  = .22) or overall survival (adjusted hazard ratio = 1.04, 95% CI = 0.96 to 1.12, P  = .35). Conclusions: We found that high-frequency surveillance does not improve outcomes in surgically treated stage I non-small cell lung cancer. Future lung cancer treatment guidelines should consider less frequent surveillance imaging in patients with stage I disease.